Long-Term Survival, Burden of Disease, and Patient-Centered Outcomes in Maximally Treated Intracerebral Hemorrhage - Mrochen, Anne; Sprügel, Maximilian; Sekita, Alexander; Balk, Stefanie; Haupenthal, David; Gerner, Stefan; Lücking, Hannes; Dörfler, Arnd; Macha, Kosmas; Schwab, Stefan; Kuramatsu, Joji; Sembill, Jochen (Annals of Clinical and Translational Neurology, 2025)
Objective: Increasing evidence shows that patients with intracerebral hemorrhage (ICH) can achieve better-than-expected outcomes with aggressive therapy. However, real-world long-term data, patient-centered outcomes, and societal measures after maximal ICH treatment are lacking. This study aimed to analyze 5-year survival, utility-weighted functional outcomes, and burden of disease in maximally treated ICH patients, stratified by max-ICH Score. Methods: This study investigated consecutive patients with spontaneous ICH included in the single-center Longitudinal Cohort Study on ICH Care (UKER-ICH, NCT03183167, 2006–2015). We included all patients without early care limitations, hereinafter referred to as maximally treated. We analyzed the stratification by max-ICH Score of cumulative 5-year survival using Kaplan–Meier estimates and COX regression modeling, disease burden using disability-adjusted life years (DALYs), and patient-centered outcome at 12 months using the Utility-Weighted modified Rankin Scale (UW-mRS). Results: The 5-year survival rate of the included 1022 maximally treated patients was 53%, stratified by max-ICH Score (0 points: 85%, 1: 91%, 2: 69%, 3: 59%, 4: 47%, 5: 32%, 6: 29%, 7: 18%, ≥ 8: 0%, log-rank p < 0.001). The mean number of DALYs was 8.94 (±8.15, standard deviation [SD]), consisting of 4.27 years of life lost (±7.79, SD) and 4.67 years lived with disability (±6.38, SD). Patients with a max-ICH Score of 5 had the highest burden of disease (12.76 [±9.43, SD]). The mean UW-mRS at 12 months was 0.45 (±0.37, SD) and decreased with increasing max-ICH Score (0: 0.80 [±0.23], 1: 0.73 [±0.29], 2: 0.67 [±0.29], 3: 0.50 [±0.34], 4: 0.39 [±0.34], 5: 0.25 [±0.30], 6: 0.19 [±0.28], 7: 0.16 [±0.26], ≥ 8: 0.08 [±0.22], p < 0.001). Interpretation: These observational data, stratified by max-ICH Score, provide patients and treating physicians with an initial severity assessment in terms of potential long-term patient-centered outcomes and burden of disease following maximal treatment.
CRIS-Team Scopus Importer:2025-04-25
Keywords: intracerebral hemorrhage prognosis; patient-centered outcomes; stroke disability burden